Use of Ceftolozane/Tazobactam in the Treatment of Multidrug-resistant Pseudomonas aeruginosa Bloodstream Infection in a Pediatric Leukemia Patient. Issue 9 (September 2016) - Aitken, Samuel L.; Kontoyiannis, Dimitrios P.; DePombo, April M.; Bhatti, Micah M.; Tverdek, Frank P.; Gettys, Suzanne C.; Nicolau, David P.; Nunez, Cesar A.
Abstract : Multidrug-resistant Pseudomonas aeruginosa is of increasing concern in pediatric patients. Ceftolozane/tazobactam is a novel cephalosporin/β-lactamase inhibitor combination with activity against multidrug-resistant Pseudomonas ; however, no data exist on its use in children. This report summarizes the treatment of a multidrug-resistant P. aeruginosa bloodstream infection in a pediatric leukemia patient with ceftolozane/tazobactam and provides the first description of its pharmacokinetics in pediatrics. Abstract : Supplemental Digital Content is available in the text.